Bioaccessibility of folate in faba bean, oat, rye and wheat matrices. (15th July 2021) - Liu, Fengyuan; Kariluoto, Susanna; Edelmann, Minnamari; Piironen, Vieno
Highlights: Folate bioaccessibility in faba bean and cereal flours and pastes was 40%−123%. In vitro folate bioaccessibility was generally better in paste than in flour. Folate was generally more bioaccessible in faba bean than it was in cereals. 5-Methyltetrahydrofolate showed better stability in faba bean than in cereals. Reduced vitamers decreased and oxidised vitamers increased during digestion. Abstract: Cereals and legumes are rich in folate. However, due to the instability of folate, processing and digestion can induce significant folate loss. In this paper, folate bioaccessibility of faba bean, oat, rye and wheat flours and pastes was studied using a static in vitro digestion model. Folate bioaccessibility depended on food matrices, varying from 42% to 67% in flours and from 40% to 123% in pastes. Digestion was associated with the interconversion of formyl folates, as well as the increase of oxidised vitamers and decrease of reduced vitamers. Especially in faba bean, 5-methyltetrahydrofolate showed surprisingly good stability both in digestion and heat treatment, resulting in high bioaccessibility. The physiological concentration of ascorbic acid did not stabilise folate in digestion; however, a higher level helped to maintain reduced vitamers. Heat treatment (10-min paste making) could improve folate bioaccessibility by liberating folate from the food matrices and by altering folate vitamer distribution.